Implementation of the Malang Mbois App as a Super-App Innovation for Enhancing Public Service Effectiveness - Imas Rostika; Ika Devy Pramudiana; Nihayatus Sholichah; Widyawati Widyawati (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study examines the implementation of the Malang Mbois app as a super-app innovation aimed at enhancing the effectiveness of public services in the city of Malang. The purpose of this research is to evaluate the extent to which the Malang Mbois app can meet expectations in improving public service efficiency and to identify the factors contributing to its success and the obstacles encountered in its implementation. A qualitative research method was employed, with data obtained from interviews with service users, city government stakeholders, and an analysis of the digital footprint of the app in daily operations. Diffusion of innovations theory served as the theoretical foundation to assess the five main characteristics of innovation: relative advantage, compatibility, complexity, trialability, and observability, all identified as key factors influencing the adoption rate of the Malang Mbois app. The findings indicate that the Malang Mbois app has successfully increased the effectiveness of public services, with 80% of users reporting enhanced satisfaction due to greater efficiency and transparency in services. Direct observation of the app demonstrated a significant reduction in the average waiting time from several weeks to just a few days for administrative processes such as business licensing. The study also identified several challenges, including the need for enhanced security infrastructure and training programs to improve digital literacy among users unfamiliar with technology. Based on these findings, it is recommended that the Malang city government intensifies efforts to integrate data, expand digital education programs, and strengthen the security of the app to support broader and sustained adoption of the Malang Mbois app. Implementing these recommendations can help address existing challenges and maximize the potential of the Malang Mbois app as an effective public service tool.